Influence of different fallow management systems on stability of soil aggregates in southern Nigeria - Salako, F.; Hauser, S. (Informa UK Limited, 2001)
The effects of different fallow management systems on aggregate stability were studied on an Ultisol and an Alfisol in southern Nigeria. Aggregate stability was measured in natural regrowth, and planted fallows of Pueraria phaseoloides Benth. and Leucaena leucocephala Lam de Wit in a trial established in 1989 on an Alfisol at Ibadan (7°30′N, 3°54′E), southwestern Nigeria. Soil samples (0–30 cm depth at this instance) were wetted by immersion for 2 and 10 minutes before wet-sieving at 30 rpm for 5 to 35 minutes at 5 minute increments. Mean-weight diameter (MWD), geometric mean diameter (GMD) and proportions of water-stable aggregates (WSA) were calculated. GMD and WSA were not affected by the length of pre-wetting or by the length of the wet-sieving period. Thus, wet-sieving for more than 5 minutes at 30 rpm was not necessary for these sandy soils. The trends observed for soil aggregate stability differed between the Alfisol and Ultisol, and for the Alfisol, it differed between a degraded and a managed fallow site. Thus, soil aggregate stability was influenced by soil type and soil management. The GMDs for the natural regrowth at 0–10 cm soil depth (0–15 cm soil depth sampling at 5 cm increment in this case) were between 1.12 and 1.42 mm, 1.14 and 1.46 mm for the Pueraria system, and 1.12 and 1.33 mm for the Leucaena system. An adjacent forest soil (0–10 cm) had GMDs between 1.24 and 1.54 mm. On a continuously cropped Alfisol, aggregate stability was significantly higher in the Pueraria live mulch system than in Leucaena alley cropping and natural regrowth. Fallowing for 2 or 3 years after 1 year cropping was essential under any of the systems to keep aggregate stability within the range of the forest soil. The fallow management practices enhanced surface soil aggregate stability.